Ultradiluted Plumbum metallicum in reversal of neurotoxicity caused by lead in Danio rerio (Research, Society and Development, 2022)
Environmental pollution caused by heavy metal residues, which are endocrine disruptors, is very relevant due to its wide use in industrial and agricultural processes. Lead is a heavy metal that is highly toxic to the environment and organisms such as fish and aquatic invertebrates. This work aims to evaluate the behavioral changes in zebrafish (Danio rerio) induced by Lead, through the analyzes of locomotor activity and anxiety parameters, verifying if homeopathic medicines are able to reduce the neurotoxic effects caused in the fish organism. The Danio rerio fishes were kept in maintenance aquariums, with controlled parameters, until the time of the experiments. The animals were exposed to heavy metal and the groups were composed of 8 animals each: white control, medication at 6cH, 30cH and inert solution, the experiment was blinded. After that, the animals underwent behavioral tests (locomotion and anxiety) to assess neurotoxicity. Lead caused anxiety in animals submitted to it with no medication (inert solution) since the time spent on the bright side of the aquarium was shorter in these animals, also reducing the distance traveled by the animals on the bright side. In the open field, the decrease in quadrants traveled by the animals that received lead without exposure to the medication is notable compared to the white control group. The group that took Plumbum metallicum 6cH had their locomotor conditions reversed, whereas the group that took Plumbum metallicum 30cH had their neurotoxicological conditions reversed.